2012
DOI: 10.18632/aging.100435
|View full text |Cite
|
Sign up to set email alerts
|

dSir2 deficiency in the fatbody, but not muscles, affects systemic insulin signaling, fat mobilization and starvation survival in flies

Abstract: Sir2 is an evolutionarily conserved NAD+ dependent protein. Although, SIRT1 has been implicated to be a key regulator of fat and glucose metabolism in mammals, the role of Sir2 in regulating organismal physiology, in invertebrates, is unclear. Drosophila has been used to study evolutionarily conserved nutrient sensing mechanisms, however, the molecular and metabolic pathways downstream to Sir2 (dSir2) are poorly understood. Here, we have knocked down endogenous dSir2 in a tissue specific manner using gene-swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 52 publications
5
53
1
Order By: Relevance
“…We have earlier shown that ablating dSir2 in the fat body results in defective fat metabolism (5). In this study, we have found that fat body dSir2-mediated changes affect lipid homeostasis, influence dilp production in the IPCs, and lead to an increase in insulin signaling in the fat body (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…We have earlier shown that ablating dSir2 in the fat body results in defective fat metabolism (5). In this study, we have found that fat body dSir2-mediated changes affect lipid homeostasis, influence dilp production in the IPCs, and lead to an increase in insulin signaling in the fat body (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Aberrations in mitochondrial functions are often associated with impaired insulin signaling. Our previous work shows that dSir2 affects insulin signaling by regulating the expression of the Drosophila insulin-like peptides (dILP2 and -5 and not the other dILPs) in a diet-dependent manner (5). To investigate if the altered mitochondrial functions observed in the results shown in Fig.…”
Section: Figmentioning
confidence: 91%
See 2 more Smart Citations
“…This was done according to the method described in [25]. For this, fat body cells from third instar Drosophila larvae were dissected out in 1X PBS (pH 7.4), fixed in 4% para-formaldehyde for 20 min at room temperature and washed twice with 1X PBS.…”
Section: Oil Red O Stainingmentioning
confidence: 99%